Territoriality Formation Through Space Utilization in Silver Craftsmen’s Houses in Celuk Village, Gianyar - I Nyoman Ananda Wijakarma (Jurnal Lingkungan Binaan Indonesia, 2026)
Celuk Village is known as a center of silver craftsmanship in Bali. The craftsmen’s houses function not only as residential spaces, but also as spaces for the production and marketing of silver craft products. This condition influences the spatial utilization pattern and the formation of territoriality within traditional Balinese houses. This study aims to analyze the relationship between space utilization and the formation of territoriality in silver craftsmen’s houses in Celuk Village, Gianyar. The study employed a descriptive qualitative approach through field observations, interviews, and spatial analysis of space utilization patterns in silver craftsmen’s houses. The results show that space utilization has adapted through the transformation of bale dauh and bale delod into production and marketing spaces, as well as the addition of production spaces in the back area (teba). These changes form a territorial structure comprising primary, secondary, and public territories, based on accessibility, spatial control, and activity functions within the house. The relationship between space utilization and territoriality reflects an adaptive process of spatial negotiation between economic needs and the preservation of local cultural values within the structure of traditional Balinese houses.